Interactive effects of irrigation and flobond on growth and yield of BRRI dhan29 (Progressive Agriculture, 2019)
The experiment was conducted at the Research Farm of Patuakhali Science and Technology University (PSTU), Patuakhali during the period from December-May of 2015 to evaluate the effect of irrigation and soil conditioner on growth and yield of BRRI dhan29. A modern HYV rice variety BRRI dhan29 was grown under four different frequency of irrigation viz., four times, six times, eight times and ten times with five rates of flobond(soil conditioner), viz., 0.0, 5.0, 10.0, 15.0 and 20.0 per plot. The experiment was laid out in a split plot design with four replications. Irrigation and rate of soil conditioner and their interaction significantly influenced the yield contributing and other crop characters. It was observed that the highest grain yield (7.08 t ha-1) was obtained from eight times irrigations, but the highest straw yield was obtained from ten times irrigations (6.706 t ha-1).The highest grain yield (7.21 t ha-1) was obtained with 10g Flobond per plot but the highest straw yield (6.29 t ha-1) was obtained with no Flobond. However, the highest grain yield (8.38 t ha-1) was obtained with eight times irrigation coupled with 10g of Flobond per plot as soil conditioner and the lowest one (5.5 t ha-1) was obtained in four times irrigation and no Flobond. So, eight times irrigation coupled with 10g of Flobond per plot as soil conditioner was the best combination for obtaining best yield.Progressive Agriculture 30 (2): 165-172, 2019